Pemanfaatan Kain Perca untuk Menghasilkan Manipulasi Kain Teknik Slashing pada Celana dengan Bahan Kulit Sintetis - Gabriella Krisnugtya Putri; Arina Haq (Garina, 2024)
The slashing technique is a technique for manipulating fabric which is done by stacking several fabrics which are treated by cutting so that later they will form a certain motif depending on the size of the cutting technique. The purpose of making this report is to find out the process of utilizing patchwork to produce fabric manipulation with slashing techniques on pants. The methodology used is qualitative method, observation method, literature study method and documentation method. The manufacture of slashing on these pants goes through several stages. In the process of making slashing, it is necessary to pay attention to when choosing a slashing pattern in order to produce the desired slashing. When making slashing, it is better to use 10 piles of material to produce a good color refraction from a pile of fabric. The arrangement of the patchwork for slashing should be a light dark color so that it gives a bold impression on the color mixing, the result of a pile of patchwork should not be too big, just around 1-1.5cm is enough. Synthetic leather as the basic material for making pants, this synthetic leather is easily damaged. When sewing synthetic leather, it is necessary to use several techniques that are quite complicated, namely large stitches, long needles and non-metallic machine shoes or you can use paper as a surface to make it easier when sewing. Also the other thing to be considered, because this is a synthethic leather fabric it will be damaged if it is exposed to a blunt needle.